Cambridge O level islamiyat paper 2 (2058/2) skills book - Sohrwardy, khalid hameed (Cambridge University Press; Karachi, 2015)
"Cambridge O-Level Islamiyat Paper 2 (2058/2) Skills Book" is a practical guide designed to enhance students' exam techniques, helping them develop the skills needed to analyze and answer questions effectively in the Cambridge Islamiyat Paper 1.